From antiquity to modern hygiene: the archaeological and medicinal legacy of lavender as a promising antimicrobial agent - Civilyte, Agne; Karanikola, Kyriaki; Kramer, Axel (GMS Hygiene and Infection Control)
Introduction: The understanding of ancient medicinal and hygienic practices using medicinal plants provides a foundation for collaboration with modern medical science. The aim of this paper is first to give a review of archaeological evidence of one of such plants – lavender, belonging to the Lamiaceae family, particularly focusing on its application for hygienic purposes. Since lavender is notable for its pharmacological and medicinal properties, offering a wide range of benefits for both physical and mental health, this is worth combining ancient experiences with the research of modern medicine. Methodology: The historical applications of lavender from antiquity to the Middle Ages were analyzed both textual and archaeobotanical evidence. Furthermore, it discusses the challenges in detecting lavender in archaeological contexts and its potential contributions to modern antiseptic medicine and heritage conservation. By combining botanical studies with modern scientific methods, we aim to reassess its role in historical medical and hygienic practices. Results: In the last two decades, following on from traditional knowledge from archaeology and antiquity, studies have been carried out on the antimicrobial effectiveness of lavender essential oils (LEO) with the result that there are potential applications for LEO for antiseptic, as combination partner in disinfectants, for preservation, impregnation and possibly also for decontamination of indoor air. Even more promising is the use of LEO in combination with antibiotics and antiseptics in order to synergistically enhance their effectiveness. Conclusion: By combining botanical studies with modern scientific methods, the role of lavender in historical medical and hygienic practices has been re-evaluated.